Congestion Management in Restructured Power Systems with Economic and Technical Considerations - R, Manikandan; P, Kavya; R, Shalini (Bulletin of Scientific Research, 2019)
In this paper, restructuring of monopolistic power systems is inevitable in this day and age to cope up with the radical growth of power demand. In developed countries restructuring is already in place while developing countries are getting accustomed to it. Above and beyond the benefits to customers in terms of economy and quality, there are several challenges prevailing particularly in transmission while exercising deregulation. The foremost challenging task of Independent System Operator (ISO) is managing the transmission line congestion in a deregulated power system. In most of the congestion management techniques, only the economic aspects are considered. The minimum voltage derivation for electronic industries and acceptable voltage derivation for high power applications are considered with suitable weighting factors in the objective function.